Biochemistry - Campbell, Mary K.; Farrell, Shawn O. (Cengage Learning, 2015)
Reflects developments in stem cell research, cloning, and immunology, and offers revised coverage of major topics, such as Molecular Biology. This book balances scientific detail with readability that's ideal for those studying biochemistry.